Cost–utility and budget impact analysis of tocilizumab for the treatment of refractory systemic juvenile idiopathic arthritis in Thailand - Nitichen Kittiratchakool; Disorn Kulpokin; Chonticha Chanjam; Soamarat Vilaiyuk; Sirirat Charuvanij; Gun Phongsamart; Parichat Khaosut; Manasita Tanya; Ratanavadee Nanagara; Sira Nantapaisarn; Pattara Leelahavarong (BMJ Open)
Objectives This study aimed to analyse the cost–utility and budget impact of adding tocilizumab to the standard treatment for patients with refractory systemic juvenile idiopathic arthritis (sJIA) in Thailand.Design Economic evaluation using a decision-analytical model.Setting Thailand.Participants Patients with refractory sJIA who were ≥2 years old.Methods The use of tocilizumab as an add-on therapy to standard treatment was compared with standard treatment alone. A simulated health state transition model was used to estimate the lifetime costs and health outcomes from a societal perspective. Direct medical costs were collected from tertiary hospital databases while direct non-medical costs were derived from interviews. Health-related quality of life (QoL) was measured using the proxy version of three-level EuroQol five-dimensional questionnaire (EQ-5D-3L). Future costs and outcomes were discounted at an annual rate of 3%. The base case population was patients aged 9.41 years old at refractory disease onset. The results were reported as incremental cost-effectiveness ratios (ICER) in US dollar (USD). One-way and probabilistic sensitivity analysis were conducted to investigate parameter uncertainty. The 5-year budget impact was estimated from a governmental perspective.Results The ICER of standard treatment plus tocilizumab was US$35 799 per quality-adjusted life-year (QALY) gained compared with standard treatment alone, which was not cost-effective at the threshold of US$5128 per QALY gained. The estimated 5 years budget impact was approximately US$4.8 million.Conclusions The use of standard treatment plus tocilizumab was not cost-effective in the Thai context, which has limited data. However, there is currently no second-line treatment for refractory sJIA in the Thai National List of Essential Medicines; thus, patients must receive higher doses of standard treatment which can cause many side effects. In contrast, tocilizumab showed obvious efficacy in clinical trials in improving treatment response and QoL. Therefore, the price of tocilizumab should be negotiated to reduce the financial impact on the healthcare system.